2023
DOI: 10.3390/nu15214686
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fisetin in Selected Malignant Neoplasms in Women

Anna Markowska,
Michał Antoszczak,
Karol Kacprzak
et al.

Abstract: A promising therapeutic window and cost-effectiveness are just two of the potential advantages of using naturally derived drugs. Fisetin (3,3′,4′,7-tetrahydroxyflavone) is a natural flavonoid of the flavonol group, commonly found in fruit and vegetables. In recent years, fisetin has gained wide attention across the scientific community because of its broad spectrum of pharmacological properties, including cytotoxic activity against most abundant cancers. By stimulating or inhibiting selected molecular targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The inhibitory effect of FIS on cholinesterases AChE and BChE has been documented in the literature [24,108]. The SAR analysis suggests that the primary factor contributing Studies on the structure-activity relationship (SAR) of FIS have been the subject of numerous literature reports [1,[98][99][100][101]. It is indicated that the three-OH group has the greatest contribution to the antioxidant properties of FIS, while the double bond between the two-and three-carbon groups, and three ′ -OH and four ′ -OH groups (B-ring) are capable of enhancing its antioxidative activity [102].…”
Section: Bchementioning
confidence: 99%
“…The inhibitory effect of FIS on cholinesterases AChE and BChE has been documented in the literature [24,108]. The SAR analysis suggests that the primary factor contributing Studies on the structure-activity relationship (SAR) of FIS have been the subject of numerous literature reports [1,[98][99][100][101]. It is indicated that the three-OH group has the greatest contribution to the antioxidant properties of FIS, while the double bond between the two-and three-carbon groups, and three ′ -OH and four ′ -OH groups (B-ring) are capable of enhancing its antioxidative activity [102].…”
Section: Bchementioning
confidence: 99%
“…Additionally, flavonoids demonstrate anticancer effects by inhibiting growth and inducing apoptosis in cancer cell lines [26][27][28][29], and have the ability to enhance cell survival in non-tumor cells [30][31][32][33]. Considered safe with a wide therapeutic window [34], flavonoids emerge as promising candidates for medical application, causing particular interest in investigating their biological effects. Recent clinical trials have shown the ability of flavonoids to improve post-COVID-19 olfactory dysfunction, reduce hypercoagulability and symptoms of rheumatoid arthritis [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Markowska et al conducted a review focusing on the anticancer properties of fisetin, a representative flavonol. Their analysis suggests that fisetin exhibits anti-cancer efficacy in female malignancies [12]. Its capacity to upregulate pro-apoptotic genes, such as caspase 3/8 and Bax, while downregulating the expression of the anti-apoptotic protein Bcl-2, is thought to be responsible for the anti-cancer effect in general.…”
mentioning
confidence: 99%
“…Additionally, investigating combination strategies, particularly those involving metabolic inhibitors, holds the potential to optimize treatment modalities or circumvent the mechanisms of drug resistance. Notably, two clinical trials are presently in the planning stages to address these aspects [12].…”
mentioning
confidence: 99%